Increased biogenesis of glucagon-containing secretory granules and glucagon secretion in BIG3-knockout mice - Hongyu Li; Tao Liu; Joy Lim; Natalia V. Gounko; Wanjin Hong; Weiping Han (Elsevier, 2015)
Objective: Although both insulin and glucagon are intimately involved in the regulation of glucose homeostasis, the intrinsic control of glucagon secretion, including the biogenesis and exocytosis of glucagon-containing granules, is far less understood compared with that of insulin. As Brefeldin A-inhibited guanine nucleotide exchange protein 3 (BIG3) is a negative regulator of insulin-granule biogenesis and insulin secretion, we investigated whether BIG3 plays any role in alpha-cells and glucagon secretion. Methods: We examined the expression of BIG3 in islet cells by immuno-fluorescence and confocal microscopy, and measured glucagon production and secretion in BIG3-depleted and wild-type mice, islets and cells. Results: BIG3 is highly expressed in pancreatic alpha-cells in addition to beta-cells, but is absent in delta-cells. Depletion of BIG3 in alpha-cells leads to elevated glucagon production and secretion. Consistently, BIG3-knockout (BKO) mice display increased glucagon release under hypoglycemic conditions. Conclusions: Together with our previous studies, the current data reveal a conserved role for BIG3 in regulating alpha- and beta-cell functions. We propose that BIG3 negatively regulates hormone production at the secretory granule biogenesis stage and that such regulatory mechanism may be used in secretory pathways of other endocrine cells.